Design of Arduino Computer Numerical Control Machine. - Mujurizi Frank (Kabale University, 2023)
This paper introduces the design of an affordable computer numerical control machine that can be used for cutting, engraving and marking on wood, acrylic and milling of wooden pieces. Machines replaced the hard to master skill of hand filing which would rake a lot of time to create a design in a work piece. CNC machines are able to produce accurate work of good quality, and in a short period of time, but these machines are quite expensive for small scale manufacturers, students and innovators. This in turn hinders the growth of small scale industries. Hence there is a need for the design of an affordable CNC machine for manufacturers and students/ innovators. In this work, designing this machine involves four methods namely; modelling of the machine in DS solidWorks, designing and selection of the materials, electronic circuit assembly and finally assembly of the mechanical structure. In this research, knowledge of machine design, solid mechanics, and strength of material and DS solidWorks is used in the selection of various machine tool components. A machine is assembled using cheap materials such as the Arduino micro controller, DC stepper motors, H-bridge motor drivers, and steel frame. After testing, the CNC machine was able to cut, engrave and mark on wood, accurately. With a smaller machine size; space is saved, the energy required to operate the machine is reduced as well, and it requires less material and components to make the machine, hence bringing down the cost greatly. The weight of moving component also comes down so that during operation, the vibration and noise are reduced. And as the machine becomes denser and lighter, it becomes more portable. With the increasing demand for small scale high precision parts in various industries, the market for small scale machine tools has grown substantially. Using small machine tools to fabricate small scale parts will provide both flexibility and efficiency in manufacturing approaches and reduce capital cost, and complexity in CNC systems which is beneficial for small business owners.